Baptisma un luterānisma attiecības Latvijas teritorijā 19. gadsimtā - Lūciņa, Endija (Latvijas Universitāte, 2009)
Latvijas teritorijā baptisms ienāk 19.gs., bet luteriskā baznīca veic asu pretreakciju. Mērķis izpētīt, kā veidojās attiecības starp baptismu un luterisko baznīcu. Darbā gaitā nonācu pie secinājumiem, ka LB izvēle pretdarboties baptistiem ir saistīta ne tikai ar iebildumiem pret baptisma mācības maldīgumu, bet arī baltvācu apdraudētību par viņu privilēģiju zaudēšanu. Arī iedzīvotāju pāriešana baptismā izraisīja ne tikai cieša pārliecība par baptisma mācības pareizumu, bet gan dažādi ārēji faktori: sociālā plaisa starp vācu mācītājiem un draudzēm, LB pastorālās aprūpes problēmas, turpretī baptisms piedāvāja cilvēkiem brīvību no LB un arī zināmas pašnoteikšanās tiesības.

SUMMARY Baptism appeared in Latvia in 19th century, but the Lutheran Church realizes a sharp opposition. The aim of my Bachelor’s Paper was to find out, how developed relationships between Baptists and the dominated Lutheran Church. After my Research, I can come to conclusion, that the choice of Lutheran Church to struggle against Baptism is connected not only with religious reasons, but also with fear of German oligarchs’ minority to lose their privileges. Also the reasons, why people converted to Baptism were not always connected with strong conviction about the rightness of Baptism doctrine, but rather was caused by Lutheran Church pastoral problems and social rift between Lutheran pastors and their congregations and some other external circumstances, while Baptism offered freedom from Lutheran Church and in a some degree self determination rights.
Relations between Baptism and Lutheranism in Latvia in 19th century
Keywords: Teoloģija un reliģiju zinātne